KOMPETENSI GURU DAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS - Djuwairiyah Djuwairiyah; Ali Fatoni; M. Holil (LP2M Universitas Ibrahimy, 2025)
There are four kinds of teacher competencies as stipulated in Government Regulation (Peraturan Pemerintah) No. 19 2005 on National Education Standard including pedagogical competence, personality competence, social competence, and professional competence. These four competencies has been a lot of discussion so they are familiar for teachers. The completely fulfillment of that four competencies in the one figure of teacher is very difficult. So hard to find figure of teacher related to four kinds of competencies, no exception to find figure of Islamic education teacher at State Senior High School 1 Asembagus (SMAN 1 Asembagus). Pedagogical competence, personality competence, social competence, and professional competence knotted inside Islamic education teacher at that school. It is recognized by students, teachers, and all employees at that school. This can be done by Islamic education teacher at State Senior High School 1 Asembagus (SMAN 1 Asembagus) because Islamic education teacher at that school is qualified in his/her level of education; he/she has high spirits to develop his/her profession; he/she has religious knowledge has been obtained at the time of studying in boarding school; and he/she has ability to interact with the others to increasing competence.